Breaking the [Sacredness] Costs in Management Accounting: Periphery Case Analysis - Binti Shofiatul Jannah; Husnul Hatimah (Universitas Hayam Wuruk Perbanas, 2022)
This study aims to explain and construct the concept of cost beyond thereasoning in mainstream accounting. This construction is carried out byredefning the cost based on the â€œperipheryâ€ case. I reference to the Nusantaraparadigm, the four principles (kaidah) in building Siraman Gong KiaiPradah methodology have been fulflled. Therefore, the method used hasbeen out of the ordinary research methods. First, it prepares a â€œperipheryâ€case to be investigated for the costs. Second, it draws the position closerto God by doing penances so that they are given instructions in reducingand classifying the data. Third, doing the charity. Fourth, it includes theâ€œvalueâ€ of the â€œperipheryâ€ case in the new cost concept. Finally, this articleproposes a change to the defnition of cost. Through the â€œperipheryâ€ case,the concept of cost transcends materialism. Cost is a number of expensesincurred, based on sincerity aimed at helping others in order to obtain thebenefts both for the world and the hereafter by prioritizing the principle ofmutual help.